Effective communication as a fundamental aspect of active aging and well-being: paying attention to the challenges older adults face in noisy environments - Heinrich, Antje; Gagné, Jean-Pierre; Viljanen, Anne; Levy, Daniel A.; Ben-David, Boaz; Schneider, Bruce A. (Mykolas Romeris University, 2016)
Successful communication is vital to active aging and well-being, yet virtually all older adults find it challenging to communicate effectively in noisy environments. The resulting discomfort and frustration can prompt withdrawal or avoidance of social situations, which, in turn, can severely limit the range of activities available to older adults and lead to a less active and satisfying lifestyle, and, in some cases, depression. Using the International Classification of Functioning, Disability and Health’s (ICF) multifactorial model (WHO, 2001), we review the wider aspects of functioning and disability as they relate to hearing difficulties and communication, placing a particular emphasis on the work we, an international and interdisciplinary group of researchers, have done in the context of the ERA-NET funded interdisciplinary HEARATTN project. The ICF model is particularly fitting because it allows us to consider how physiological changes in hearing and cognition affect listening in various situations, what the consequences of these changes are for communicative abilities and social participation, and how this in turn affects life-space mobility, self-reported well-being, and, ultimately, quality of life. We will discuss how environmental conditions (both physical and social) and personal factors can affect how well older adults can communicate in the situations characteristic of everyday life. In the concluding section we discuss some behaviors, techniques and strategies that can be adopted to maintain or improve effective communication under difficult listening conditions.